2017
DOI: 10.1016/j.actamat.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen - Dislocation interaction in zirconium from first principles

Abstract: Plasticity in zirconium alloys is mainly controlled by the interaction of 1/3 1210 screw dislocations with oxygen atoms in interstitial octahedral sites of the hexagonal close-packed lattice. This process is studied here using ab initio calculations based on the density functional theory. The atomic simulations show that a strong repulsion exists only when the O atoms lie in the dislocation core and belong to the prismatic dislocation habit plane. This is a consequence of the destruction of the octahedral site… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Comparing the present results with Ref. [26] on the interaction of screw dislocations with oxygen atoms in zirconium, we see that the same repulsive interaction resulting from the destruction of oxygen insertion sites by the stacking fault ribbon and leading to a change of dislocation core configuration is obtained in zirconium and titanium when the oxygen atom lies in its natural octahedral insertion sites. Therefore, in both metals, the screw dislocations gliding in prismatic planes undergo a stronger lattice friction because of the creation of jogs allowing to bypass the solute atoms.…”
Section: Initial Configurationsupporting
confidence: 82%
See 1 more Smart Citation
“…Comparing the present results with Ref. [26] on the interaction of screw dislocations with oxygen atoms in zirconium, we see that the same repulsive interaction resulting from the destruction of oxygen insertion sites by the stacking fault ribbon and leading to a change of dislocation core configuration is obtained in zirconium and titanium when the oxygen atom lies in its natural octahedral insertion sites. Therefore, in both metals, the screw dislocations gliding in prismatic planes undergo a stronger lattice friction because of the creation of jogs allowing to bypass the solute atoms.…”
Section: Initial Configurationsupporting
confidence: 82%
“…1). These interstitial sites correspond to octahedral sites in the twined hcp crystal [26], since the pyramidal fault is a two-layer twin in the pyramidal stacking [28,29]. Both the pyramidal and mixed pyramidal-prismatic cores relax towards the same core shown in Figs.…”
Section: Initial Configurationmentioning
confidence: 92%
“…This phenomenon indicates that a repulsive force exists between the O atom and the basal dislocation core. To verify this point, the interaction energy between oxygen and screw <a> dislocation core was computed in term of Equation (1) defined as [9,10,29]:…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, using ab initio calculations, Ventelon et al [8] found that carbon atoms would induce the reconstruction of screw dislocation core in Fe, and therefore be accountable for the solute-segregation related phenomena, such as yielding and strain aging in Fe-C alloy systems. Moreover, in the other two hexagonal close-packed (HCP) metals, Zr and Ti, researchers have discovered that interstitial oxygen atoms would increase the lattice friction against the glide of screw dislocation, thus significantly influencing the plasticity of Zr and Ti [9][10][11]. The aforementioned studies on interstitial nonmetallic alloying elements invoke us to speculate whether the mechanical properties of Mg can be tuned by the solutionization of nonmetallic elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation